CURRENT PRIORITIES AND GOALS FOR SUSTAINABLE DEVELOPMENT IN DEVELOPING COUNTRIES - Поліна Олександрівна Подлепіна (Збірник наукових праць Черкаського державного технологічного університету: Серія: Економічні науки, 2019)
This paper identifies the globalization priorities of developing countries. The purpose of this article is to determine the impact of international tourism on the current priorities of sustainable development in developing countries. In the second quarter of the 21st century, the tourism industry has proven its ability, in particular, to promote economic development and job creation. It should be noted that tourism accounts for 15% of world GDP, 11% of trade and one of 11 jobs created, making tourism an important socio-economic segment of the world economy. It should be remembered that more than 1.2 billion people cross the borders of different countries a year, so tourism has become a vital basis for inter-ethnic dialogue, the sharing of world cultural heritage, social integration, peace, and, on this basis, sustainable development. Therefore, there is a diversification of the tourism industry in terms of new directions and system-forming markets, the growing impact of technology and changing consumer needs, among which the desire for authenticity and adherence to world experience should be emphasized. Due to its growth and multifaceted nature, tourism has become a powerful force in promoting sustainable development in three main areas: economic, social and environmental. Its important role in the development of the world economy has been recognized, as already mentioned, by bringing tourism to the list of industries that can contribute to the achievement of these sustainable development goals. The author has identified the place and role of tourism in achieving the 17 Sustainable Development Goals in 2030 Transformation Countries. The analysis of the difficulties faced by the tourism industry of developing countries is carried out. Cause-and-effect relationships have been justified in shaping the socio-economic development of developing countries. The article investigates the structural and logical foundations of sustainable development on the basis of synergy, regarding the use of tourism potential. The author defined the nature and main principles of sustainable tourism development in developing countries.